The Use of Ultrasound as a Potential Adjunct to Cell-Free Fetal DNA Screening for Aneuploidy at Weill Cornell Medical College, New York, USA - Scholl, Jessica; Chasen, Stephen (The Surgery Journal, 2018)
Objective To evaluate the utility of ultrasound in identifying fetuses with uncommon chromosomal abnormalities that would be considered not detectable by cell-free fetal deoxyribonucleic acid (cfDNA).Study Design We performed a retrospective study of fetuses with chromosomal abnormalities that would be undetectable by cfDNA, who underwent an 11- to 14-week ultrasound from 2006 to 2016.Results There were 43 pregnancies included. First-trimester ultrasound revealed a fetal abnormality in 19 (44.2%) cases, of which 13 (30.2%) had a thickened nuchal translucency. There were an additional four fetuses with second-trimester sonographic abnormalities. Overall, 23 (53.5%) fetuses were found to have a major anomaly diagnosed by ultrasound. The rate of first-trimester sonographic abnormalities varied widely based on category of chromosomal abnormalities with high rates seen with triploidy (87.5%) and autosomal trisomy (80%) and lower rates seen with structurally abnormal chromosomes (33.3%), trisomy mosaicism (27.3%), other forms of mosaicism (11.1%), and deletions or duplications (25.0%), p < 0.001.Conclusion The majority of fetuses with uncommon chromosomal abnormalities in our cohort had major sonographic anomalies. The use of first-trimester ultrasound with nuchal translucency measurement may offer utility in identifying fetuses with risk of aneuploidy that would not be detectable with cfDNA.
Keywords: Cell-free fetal DNA; prenatal cytogenetics; fetal ultrasound; nuchal translucency